A REVIEW OF HUMAN RIGHTS OF TRIBAL CHILDREN: POLICY IMPLICATIONS IN THE GLOBALIZATION ERA - Gathia, Joseph (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 1998)
Human dignity and integrity are the symbolic concepts at the centre of the ethical system comprising the social values that are the essence of human rights. The paper traces the Indian heritage of human rights and links this with the Universal Declaration of Human Rights and pleads that human rights are not a Eurocentric idea. Contrary to the prevalent notion among NGOs that the Child’s Rights Convention is the only instrument which provides for the rights of children, the paper argues that the Universal Declaration on Human Rights provides a more holistic approach, as well as opportunities to the children from marginalized groups, particularly tribal children.The paper is divided into five parts. Part one deals with the origin and cultural factors of human rights and the role of Universal Declaration on Human Rights in promoting and providing human rights of marginalized groups such as tribal communities. Part two deals with the situation of tribal children with particular reference to girls in India. Part three discusses the legal provisions and the effect of the CRC and UDHR. Part four deals with the micro level experiments and experiences, and, finally, part five with the policy implications for future action. The paper concludes with a note that strengthening grassroots democratic institutions is an important action, which needs to be on the agenda in the next millennium. The UDHR, rather than CRC and CEDAW, may play a more affirmative role because of their more holistic approaches, encompassing civil and political rights as well as cultural, economic and social rights. The paper also briefly sheds light on the effect of a market economy on tribal children.